PENGARUH SENAM IBU HAMIL TERHADAP KADAR HEMOGLOBIN PADA IBU HAMIL - Jayani, Indah; Susmiati; Novita Agnes, Yeni Lufiana; Ramayanti, Eva Dwi; Sulistyoning Suharto, Idola Perdana; Sisilia Enge, Charolina (Nursing Sciences Journal, 2024)
Anemia in pregnancy is a condition where pregnant women have hemoglobin (Hb) levels below normal values, which has a serious impact on the growth and development of the fetus. One non-pharmacological therapy that can be given to pregnant women is through pregnancy exercises. The aim of this study was to determine the effect of pregnancy exercise on Hb levels in pregnant women. This research design used experimental research. The population of this research was 40 pregnant women at the Jeli Community Health Center, Karangrejo District, Tulungagung Regency and with a purposive sampling technique, a sample of 37 people was obtained. Data analysis used paired t-test. The results of the study showed that the average Hb level in pregnant women before pregnancy was 11.7 g/dl and after the pregnancy exercise intervention the average was 12.5 g/dl. The results of statistical tests using the paired t-test obtained a significance value (p value=0.000 < a=0.05. So it can be concluded that there is an influence of pregnancy exercise on Hb levels in pregnant women. It is hoped that pregnant women will carry out routine pregnancy exercise as an effort to control Hb levels..  Keywords : pregnant_women, hemoglobin_levels, pregnancy_exercise